Understanding the influence of culture on the relationship between rewards and organizational commitment in Chinese business: A study of China Airline Co - Muress, Stuart (2009)
This work examines the influence of culture on the relationship between rewards and organizational commitment in a Chinese business, China Airline Co*. First the research gives an overview of the airline industry in China and highlights the significance of this research in a Chinese context. The literature review then evaluates existing literature on organizational commitment in the West and within China before the hypotheses are developed. Quantitative research was undertaken, in the form of questionnaires distributed to employees of China Airline Co and this data has been analysed. Finally, the conclusion and limitations of the study are presented.